Role of funders in embedding tests in conservation practice - Rebecca K. Smith; Nancy Ockendon; Nida Al‐Fulaij; Alessandro Badalotti; Rachel Beattie; James Byrne; Sophia Cooke; Tiago de Zoeten; Winifred F. Frick; Stephan M. Funk; Douglas Gibbs; Lauren Gupta; et al. (Conservation Biology, 2026)
Effective conservation practice requires decisions based on reliable and relevant evidence, but significant gaps in the evidence base exist. Incorporating well‐designed tests of the effectiveness of interventions for biodiversity in conservation projects is one of the best ways to scale up the rate of evidence generation. Funders of conservation projects are uniquely positioned to support and incentivize such tests as part of the grant‐making process. Using a structured process, as 25 conservation funders and members of Conservation Evidence, we identified means of improving the effectiveness of the work funded through the support of enhanced evidence generation. We identified 11 approaches through which funders can support embedding testing, ranging from encouraging inclusion of a test in the project proposal, to designating separate funds for incorporating a test, to supporting an external testing unit to provide training and advice. The appropriate approaches vary depending on the scale, process, and type of funding. Barriers to supporting testing and potential solutions were discussed, barriers such as a lack of skills to check tests are appropriate and well designed and the additional time needed to develop, implement, and see outcomes of tests and differing types of projects. By encouraging testing of actions as part of conservation practice (where appropriate), funders will ultimately facilitate a stronger evidence base for more effective decision‐making and better outcomes for nature and society.